Antiedemic Effect of the Myosin Light Chain Kinase Inhibitor PIK7 in the Rat Model of Myocardial Ischemia Reperfusion Injury - Dmitry L. Sonin; Mikhail S. Medved; Asker Y. Khapchaev; Maria V. Sidorova; Marina E. Palkeeva; Olga A. Kazakova; Garry V. Papayan; Daniil A. Mochalov; Sarkis M. Minasyan; Ilya E. Anufriev; Daria V. Mukhametdinova; Natalia M. Paramonova; et al. (Current Issues in Molecular Biology)
Myocardial ischemia-reperfusion injury increases myocardial microvascular permeability, leading to enhanced microvascular filtration and interstitial fluid accumulation that is associated with greater microvascular obstruction and inadequate myocardial perfusion. A burst of reactive oxygen species and inflammatory mediators during reperfusion causes myosin light chain kinase (MLCK)-dependent endothelial hyperpermeability, which is considered a preventable cause of reperfusion injury. In the present study, a single intravenous injection of MLCK peptide inhibitor PIK7 (2.5 mg/kg or 40 mg/kg) was found to suppress the vascular hyperpermeability caused by ischemia/reperfusion injury in an in vivo rat model. The antiedemic effect of PIK7 is transient and ceases within 90 min of reperfusion. The early no-reflow detected for the first time after 30 min ischemia in this model of myocardial infarction reduces the area accessible for PIK7. Electron microscopy has shown membrane-bound blebs of endotheliocytes, which partially or completely obturate the capillary lumen, and few capillaries with signs of intercellular gap formation in samples obtained from the center of the early no-reflow zone in control and PIK7-injected rats. Co-injection of PIK7 with NO donor sodium nitroprusside (SNP) increases blood flow in the zone of early no-reflow, while reducing the increased vascular permeability caused by SNP.